2011
DOI: 10.1200/jco.2011.29.27_suppl.40
|View full text |Cite
|
Sign up to set email alerts
|

Predicting nipple-areolar involvement using preoperative breast MRI and primary tumor characteristics.

Abstract: 40 Background: Preoperative assessment of the nipple-areolar complex (NAC) is invaluable when considering nipple-sparing mastectomy (NSM). We hypothesized that breast MRI could predict involvement of the NAC with tumor. Methods: We compiled clinical, pathologic and imaging data for patients who underwent preoperative breast MRI followed by mastectomy or NSM between 2006 and 2009. Blinded rereview of all MRI studies was performed by a breast MRI imager and compared to initial MRI findings. Multivariate analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 0 publications
5
15
0
Order By: Relevance
“…To the best of our knowledge, the only similar prospective study reported a sensitivity of 28% and a specificity of 100% for the initial MRI report, while a blinded re-review of all MRI scans Table 3 Diagnostic performance of preoperative MRI assessment, intraoperative pathological assessment and combined assessment on the prediction of NAC involvement. looking specifically for NAC involvement increased sensitivity to 56% and lowered specificity to 95% [19]. Our study confirms the crucial role of intra-operative pathological assessment of the NAC whose diagnostic performance was as good as that of the combined assessment (MRI + pathological), except for a lower sensitivity.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…To the best of our knowledge, the only similar prospective study reported a sensitivity of 28% and a specificity of 100% for the initial MRI report, while a blinded re-review of all MRI scans Table 3 Diagnostic performance of preoperative MRI assessment, intraoperative pathological assessment and combined assessment on the prediction of NAC involvement. looking specifically for NAC involvement increased sensitivity to 56% and lowered specificity to 95% [19]. Our study confirms the crucial role of intra-operative pathological assessment of the NAC whose diagnostic performance was as good as that of the combined assessment (MRI + pathological), except for a lower sensitivity.…”
Section: Discussionsupporting
confidence: 77%
“…The higher figure of NAC involvement in the current series may be due to a pathological protocol specifically aimed at assessing tumour infiltration of SD and ND, whereas the protocol of our previous retrospective study relied on a standard pathological assessment of the NAC [18]. Indeed, other studies of NAC sparing mastectomy with similar criteria of pathological assessment show NAC involvement rates comparable to our current study [19]. In order to facilitate surgical planning, other groups have explored the relationship of several preoperative clinical and radiological parameters with the likelihood of NAC involvement (Table 4).…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations